2018
DOI: 10.2196/10821
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an eHealth Intervention to Reduce Sickness Absence Frequency Among Employees With Frequent Sickness Absence: Randomized Controlled Trial

Abstract: BackgroundFrequent sickness absence—that is, 3 or more episodes of sickness absence in 1 year—is a problem for employers and employees. Many employees who have had frequent sickness absence in a prior year also have frequent sickness absence in subsequent years: 39% in the first follow-up year and 61% within 4 years. Moreover, 19% have long-term sickness absence (≥6 weeks) in the first follow-up year and 50% within 4 years. We developed an electronic health (eHealth) intervention, consisting of fully automated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…SA is a complex, multifactorial phenomenon, which often has personal, workrelated, and social determinants [9,10]. For the prevention of SA, return to work strategies to prevent SA, as well interventions based on principles of universal or selective prevention (which only focus on one or two explaining factors) appear to be less effective [8,11,12]. Because often due to the multifactorial etiology of SA, a more comprehensive approach is needed [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…SA is a complex, multifactorial phenomenon, which often has personal, workrelated, and social determinants [9,10]. For the prevention of SA, return to work strategies to prevent SA, as well interventions based on principles of universal or selective prevention (which only focus on one or two explaining factors) appear to be less effective [8,11,12]. Because often due to the multifactorial etiology of SA, a more comprehensive approach is needed [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Ten studies were RCTs evaluating the effect of eHealth interventions on the duration of sick leave. 8 , 22 , 26 , 53 - 59 One study used qualitative interviews, 60 one study used a time-series analysis, 61 and one study used a mixed methods design. 7 In four studies, the main aim was to explore the feasibility or acceptability of the eHealth intervention.…”
Section: Resultsmentioning
confidence: 99%
“… 7 Three of the identified studies reported on an eHealth intervention for employees sick-listed due to various diagnoses; one of the studies included employees with musculoskeletal pain, fatigue, or common mental disorders, 56 and two studies included employees sick-listed due to any type of diagnosis. 26 , 61 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Musculoskeletal disorders and stress-related ill health are seen as the most important reasons for LTSA (8,9). However, the etiology of SA is often multifactorial which makes it difficult to comprehend and requires a holistic understanding (10)(11)(12). Many factors have been associated with an increased LTSA risk, for example, age, gender, lifestyle, poor health, SA records, physical workload, and psychosocial working conditions (10,(13)(14)(15).…”
mentioning
confidence: 99%